Vitagraph : America's first great motion picture studio - Erish, Andrew A., 1958- (Screen classics (Lexington, Ky.), 2021)
"The widely accepted history of the American film industry holds that the founders of Paramount and Fox invented the feature film, that Universal created the star system, and that these three companies (along with the heads of MGM and Warner Bros.) were responsible for developing the multi-billion-dollar business that came to dominate the cinematic world. This account has been repeated continuously for nearly a century, but it simply isn't true. In Vitagraph, Andrew A. Erish presents an important reassessment of the birth and development of motion pictures in America by offering the definitive history of a significant yet forgotten studio. Founded in 1897 by James Stuart Blackton and Albert Edward Smith, the Vitagraph Company of America (later known as Vitagraph Studios) was largely responsible for the birth of American cinema. By 1907, it was one of the largest film studios in America and produced dozens of movies annually. The company's notable works include the first film adaptation of Les Misérables; many movies featuring the popular comedian John Bunny; The Military Air-Scout (1911) which is considered to be the first aviation film; and the World War I propaganda film The Battle Cry of Peace (1915). In 1925, Warner Bros. purchased Vitagraph and all of its subsidiaries and began to rewrite the history of American cinema. Erish challenges the creation myths marketed by Hollywood's conquering moguls-finally providing an accurate and inclusive account of the largest and most influential producer of silent era motion pictures. Drawing on valuable primary material overlooked by other historians, he introduces readers to many fascinating yet forgotten pioneers and offers a much-needed correction to the history of commercial cinema"--